Quality evaluation of concrete structures: Some nondestructive testing approaches - Aryal, Mohan Prasad (Nepalese Journal of Engineering, 2005)
Evaluation of concrete strength in a built-up structure is a major concern to assess conditions of structure with time. In this work some correlations between destructive and nondestructive parameters have been identified. Compressive and tensile strengths are adopted as destructive parameters, whereas rebound numbers and ultrasonic pulse velocity – as nondestructive parameters. The data are limited to concrete grades M20, M30 and M40 with six sets of aggregates widely used in the construction works in Nepal. The data will be helpful in identifying the variations in strength and strength related properties of concrete in already constructed structures and adopt appropriate measures for necessary interventions - maintenance, retrofitting and others in their life time. Keywords: design strength, destructive testing, nondestructive testing, calibration chart. Nepalese Journal of Engineering Vol.1(1) 2005 pp.80-83